2005
DOI: 10.1177/216507990505300805
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation—Part III: Pharmacotherapy of Smoking Cessation

Abstract: T obacco dependence is a chronic condition with efficient and cost-effective treatment available. All tobacco users should be offered one of the first-line agents for smoking cessation, except in special circumstances (Fiore, Bailey, & Cohen, 2000). Misconceptions and fears of using medications, for smoking cessation have greatly contributed to the under-utilization of these products. This is the third column in a three-part series on smoking cessation. This column addresses the various pharmacological agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This effect facilitates allergen penetration across the epithelium and augments histamine release from subepithelial sensitized basophils [24]. Further, tobacco smoke exposure increases secretion of the proallergic cytokine, thymic stromal lymphopoietin (TSLP) in lung tissue [2527]. TSLP is a cytokine that influences development of Th2 cells through upregulation of OX40 ligand in dendritic cells and is now considered to be critical in development of atopic responses [28].…”
Section: Adverse Effects Of Tobacco Smoke Exposure On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect facilitates allergen penetration across the epithelium and augments histamine release from subepithelial sensitized basophils [24]. Further, tobacco smoke exposure increases secretion of the proallergic cytokine, thymic stromal lymphopoietin (TSLP) in lung tissue [2527]. TSLP is a cytokine that influences development of Th2 cells through upregulation of OX40 ligand in dendritic cells and is now considered to be critical in development of atopic responses [28].…”
Section: Adverse Effects Of Tobacco Smoke Exposure On the Immune Systemmentioning
confidence: 99%
“…Studies have shown that NRTs increase the odds of long-term cessation by 1.5- to 2-fold. NRTs are specifically designed to relieve some of the nicotine withdrawal symptoms and have also been found to serve as good adjuvants to the nicotine-free medications, including bupropion and varenicline [27, 5054]. Bupropion is a heterocyclic antidepressant that has been specifically marketed for smoking cessation.…”
Section: Practical Strategies To Assist Parents With Smoking Cessationmentioning
confidence: 99%
“…By providing nicotine throughout the night, the 24-hour patch reduces cravings for the fi rst cigarette in the morning. 30 Some patients experience vivid dreams or insomnia when the patch is worn for 24 hours. Wearing the patch for 16 hours and removing it at night may alleviate both issues.…”
Section: Nicotine Patchmentioning
confidence: 99%
“…The FDA has not yet approved an NRT combination treatment, but existing studies on combination treatments do show some advantages over single or no medications at all. 30,[46][47][48][49] Combination therapy for smoking cessation usually includes combining a passive NRT, such as the patch, with an acute NRT, such as the gum (as mentioned earlier). Adding nicotine gum to the patch has been shown to improve quit rates from 23% to 34% at 12 weeks and from 15% to 28% at 24 weeks.…”
Section: Combination Therapymentioning
confidence: 99%